Funding of University Education in Nigeria and COVID-19 Pandemic: 7 Educational Managers’ Transformational Lens - Nurudeen Olalekan , Orunbon; Modupe, saac-Philips Margaret; Abiona , Ibikunle Ganiyu (International Journal of Educational Management, 2025)
The recent outbreak of the CO/ID-19 pandemic has widened disparities around the globe in the education industry. Although COVID-19 remains novel, its effect on humanity as a whole is an unparalleled trauma. In order to contain and curtain the COVID-19 pandemic, the academic programmes of schools in many countries around the world have been interrupted. Because of this pandemic, school closures have caused untold academic distress for students. Protecting education budgets has never been more important. According to records, the Nigerian education budget has not met the UNESCO-recommended 10 to 15% of the budget in developing countries for the past ten years. Lack of funding for University education would have an effect on broader development issues such as health, technology, poverty, and economic growth, as well as young people’s empowerment.This study therefore x-rays the strategies for university administrators to diversify the ways in which their universities are financially maintained, as the state is not prepared to be solely responsible for the provision of the higher education fund. The COVID-19 pandemic has revealed the weak condition of our education sector and has had a negative effect on its efficiency. Through their successions, government has paid lip service to education by not significantly investing in the industry.